Polyacrylic acid binder, preparation method thereof and lithium ion battery

By using polyacrylic powder adhesive in lithium-ion batteries, the problem of insufficient force of the adhesive and negative electrode materials in the prior art is solved, better circulation performance and low temperature performance are achieved, and the adhesion and expansion resistance of the battery are enhanced.

CN119505762AActive Publication Date: 2025-02-25WANHUA CHEM GRP BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411730253.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-08
Filing Date
2024-11-28
Publication Date
2025-02-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The styrene butadiene rubber solution (SBR) and carboxymethyl cellulose (CMC) used in existing lithium-ion batteries are used as binders, resulting in weaker force with the negative electrode material, especially in low temperature conditions, which makes it difficult to meet the requirements.

Method used

The polyacrylic acid (PAA) powder binder is prepared by neutralizing the polyacrylic acid powder binder with high polar functional groups by neutralizing the alcohol solvent, which is suitable for the dry electrode homogenization process.

Benefits of technology

It improves the circulation performance and low temperature performance of lithium-ion batteries, enhances the adhesion and ability to suppress expansion, and improves the processing yield of electrode sheets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of new energy, in particular to a polyacrylic acid binder, a preparation method thereof and a lithium ion battery. The preparation method of the polyacrylic acid powder binder comprises the following steps: mixing a polymeric monomer and an initiator, and carrying out a polymerization reaction to prepare a polyacrylic acid copolymer; and in the presence of an alcohol solvent, carrying out neutralization treatment on the polyacrylic acid copolymer at the temperature of not more than 60 DEG C to obtain the polyacrylic acid powder binder. According to the present invention, in the presence of the alcohol solvent, the neutralization treatment is performed at the temperature of not more than 60 DEG C, such that the obtained powder binder can adapt to the subsequent dry method homogenization process, has good adhesion, and can easily inhibit the volume expansion of the electrode plate so as to improve the cycle performance of the lithium ion battery. Meanwhile, if the alcohol solvent can remain, the flexibility of the binder can be improved, and the processing yield of the electrode plate can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a polyacrylic acid binder and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Lithium-ion batteries are widely used in electronic products, electric vehicles, energy storage equipment and other fields due to their high energy density, long cycle life and easy design. As the application scenarios and functional requirements of various products become increasingly diverse, the market has also put forward higher requirements for the energy density, reliability and cost of lithium-ion batteries.

[0003] Binder is an important material in lithium-ion batteries. Its main function is to adhere the electrode active material and conductive agent to the current collector. Although the amount of binder is not much, its performance has an important impact on the performance of lithium batteries.

[0004] At present, styrene-butadiene rubber solution (SBR) is widely used as a binder, and carboxymethyl cellulose (CMC) needs to be added as a thickening dispersant during its use. However, due to its material composition, the content of polar functional groups such as carboxyl, ester and cyano groups contained in SBR / CMC is limited, and the interaction between it and the negative electrode material, especially the silicon-carbon negative electrode, is weak. Therefore, the comprehensive performance of the battery, especially the low-temperature performance, has become increasingly difficult to meet the application requirements.

[0005] Polyacrylic acid (PAA) binders contain a high content of polar functional groups in the polymer. During the charge and discharge process, there is a complexation and decomplexation between the polar functional groups and lithium ions, which can promote lithium ion conduction and reduce the internal resistance of the battery. However, polyacrylic acid itself has an ultra-high molecular weight, and its viscosity in the aqueous phase is very high, and it is difficult to increase the solid content, resulting in an increase in the transportation and packaging costs of polyacrylic acid solution-type binders. Compared with solution-type binders, the transportation and packaging costs of powder binders are lower, but the current powder binders cannot adapt well to the dry slurry process in the preparation of electrode slurry, which affects the performance of the battery. Summary of the invention

[0006] Based on this, the first aspect of the present application provides a method for preparing a polyacrylic acid powder binder, and its technical solution is as follows:

[0007] A method for preparing a polyacrylic acid powder binder comprises the following steps:

[0008] Mixing polymerization monomers and initiators to generate polymerization reaction to prepare polyacrylic acid copolymers;

[0009] In the presence of an alcohol solvent, the polyacrylic acid copolymer is neutralized at a temperature not exceeding 60° C. to obtain a polyacrylic acid powder binder.

[0010] This application has been verified through experiments and found that in the preparation process of polyacrylic acid powder binder, the operation of neutralization treatment has an important influence on the ability of subsequent powder binder to adapt to dry electrode homogenization. In the presence of alcohol solvent, this application performs neutralization treatment at a temperature not exceeding 60°C, and the reaction is milder, avoiding the problem that the powder binder is difficult to redissolve in the aqueous slurry due to neutralization treatment at high temperature, resulting in homogenization difficulties and the inability to prepare electrodes. In addition, alcohol solvents can also be used as dissolution inhibitors of polyacrylic acid copolymers to improve the hydration problem of polyacrylic acid copolymers during low-temperature neutralization, so as to smoothly obtain powder binders, avoid forced drying of the powder binders to interfere with the stability of subsequent dry homogenization, and thus have significantly improved bonding force and the ability to inhibit expansion, which can effectively inhibit the volume expansion of active substances in the charge and discharge cycle, thereby improving the cycle performance of electrode plates and lithium-ion batteries. At the same time, if the alcohol solvent can remain in the polyacrylic acid powder binder, it is also beneficial to increase the flexibility of the binder, improve the hard and brittle characteristics of the binder, improve die-cutting dropout, and improve the processing yield rate of electrode plates.

[0011] Optionally, the alcohol solvent has no less than 3 carbon atoms.

[0012] Optionally, the alcohol solvent has a carbon number between 3 and 6. For example, the alcohol solvent has a carbon number of 3, 4, 5, or 6.

[0013] Optionally, the alcohol solvent is selected from one or more of 1,3-butanediol, 1,4-butanediol, 1,2-propylene glycol, 1,2-pentanediol, pentaerythritol, isopropanol, glycerol, 1-butanol, 1-pentanol, 2-butanol and 1-hexanol.

[0014] Optionally, the mass of the alcohol solvent is not less than the total mass of the polymerized monomers. If the amount of alcohol solvent added is less than the total mass of the polymerized monomers, the dissolution inhibition effect on the polyacrylic acid copolymer is relatively poor, which will cause the polyacrylic acid copolymer to hydrate during the neutralization treatment to form a viscous paste, increase the difficulty of drying to obtain a powder binder, and if forced drying is required, the drying time needs to be extended, which will produce a small amount of insoluble matter, aggravate the instability of the homogenate, affect the bonding force and the ability to inhibit expansion, and affect the battery performance. Optionally, the mass of the alcohol solvent is 1 to 3 times the total mass of the polymerized monomers. For example, the mass of the alcohol solvent is 1 times, 2 times, or 3 times the total mass of the polymerized monomers. If the amount of alcohol solvent added is too much, the energy consumption cost of recycling will increase.

[0015] In the present application, the temperature of the neutralization treatment does not exceed 60° C. For example, the temperature of the neutralization treatment is 10° C., 20° C., 30° C., 40° C., 50° C., and 60° C. When the temperature of the neutralization treatment is too high, PAA will self-crosslink, and during dry homogenization, the powder binder will be difficult to redissolve in the aqueous slurry, and gel or insoluble matter will appear, affecting the preparation of the electrode.

[0016] Optionally, after the neutralization treatment, the method further comprises the following steps: separating the solid and liquid of the reaction system after the neutralization treatment, and partially drying the obtained solid. In order to cooperate with the subsequent dry homogenization process, the solid is partially dried.

[0017] Optionally, the temperature of incomplete drying does not exceed 80° C. For example, the temperature of incomplete drying is 40° C., 50° C., 60° C., 70° C., 80° C. Controlling the temperature of incomplete drying is conducive to obtaining a powder binder that is better suitable for the dry homogenization process.

[0018] Optionally, the incomplete drying condition is controlled so that the solid content of the polyacrylic acid powder binder is 90wt% to 99wt%. For example, the solid content of the polyacrylic acid powder binder is 90wt%, 92wt%, 95wt%, 98wt%, or 99wt%. The above solid content is conducive to subsequent dry homogenization.

[0019] When the number of carbon atoms in the alcohol solvent is large, for example, the number of carbon atoms is 6, the alcohol solvent is not easy to volatilize in the subsequent incomplete drying process, and the alcohol solvent content remaining in the polyacrylic acid powder binder is large. Optionally, the content of the residual alcohol solvent in the polyacrylic acid powder binder is greater than or equal to 0.3wt%. Optionally, the content of the residual alcohol solvent in the polyacrylic acid powder binder is 0.3wt%~8wt%. For example, the content of the residual alcohol solvent in the polyacrylic acid powder binder is 0.3wt%, 0.5wt%, 2wt%, 5wt%, and 8wt%. The residual alcohol solvent can be used as a plasticizer, which is beneficial to increase the flexibility of the binder, improve the hard and brittle characteristics of the binder, improve die-cutting dropout, and improve the processing yield of the electrode plate.

[0020] When the number of carbon atoms in the alcohol solvent is small, for example, the number of carbon atoms is 3, the alcohol solvent is easy to volatilize in the subsequent incomplete drying process, and the alcohol solvent content remaining in the polyacrylic acid powder binder is small. In order to improve the flexibility of the binder, optionally, after incomplete drying, the following steps are also included: the alcohol solvent content added to the polyacrylic acid powder binder is greater than or equal to 0.3wt%; optionally, the alcohol solvent content added to the polyacrylic acid powder binder is 0.3wt%~8wt%. For example, the alcohol solvent content added to the polyacrylic acid powder binder is 0.3wt%, 0.5wt%, 2wt%, 5wt%, and 8wt%. By adding alcohol solvent, it is beneficial to increase the flexibility of the binder, improve the hard and brittle characteristics of the binder, improve die-cutting dropout, and improve the processing yield of the electrode plate.

[0021] Optionally, the method of adding the alcohol solvent is to spray the alcohol solvent onto the powder in the form of a spray.

[0022] Optionally, the conditions of the polymerization reaction and the neutralization treatment are controlled so that the weight average molecular weight (Mw) of the polyacrylic acid powder binder is between 600,000 and 2.5 million. For example, the weight average molecular weight of the polyacrylic acid powder binder is 600,000, 700,000, 900,000, 1.2 million, 1.5 million, 2 million, 2.4 million, or 2.5 million.

[0023] Optionally, the conditions of the polymerization reaction and the neutralization treatment are controlled so that the molecular weight distribution of the polyacrylic acid powder binder is between 1.5 and 6. For example, the molecular weight distribution of the polyacrylic acid powder binder is 1.5, 1.8, 2, 3, 5, 6.

[0024] Optionally, the pH value of the neutralization treatment system is 6 to 9. For example, the pH value of the neutralization treatment system is 6, 7, 8, 9.

[0025] Optionally, the neutralizing agent of the neutralization treatment comprises an alkaline substance. Optionally, the alkaline substance comprises an inorganic base. Optionally, the inorganic base comprises one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate and potassium carbonate.

[0026] Optionally, the polymerizable monomers include carboxyl-containing polymerizable monomers, amide-containing polymerizable monomers, and nitrile-containing polymerizable monomers. Optionally, the polymerizable monomers further include phosphorus-containing polymerizable monomers. In some examples, the polymerizable monomers include carboxyl-containing polymerizable monomers, amide-containing polymerizable monomers, nitrile-containing polymerizable monomers, and phosphorus-containing polymerizable monomers;

[0027] Optionally, the carboxyl-containing polymerizable monomer accounts for 20wt% to 40wt% of the total amount of the polymerizable monomers, the amide-containing polymerizable monomer accounts for 10-35wt% of the total amount of the polymerizable monomers, the nitrile-containing polymerizable monomer accounts for 40-50wt% of the total amount of the polymerizable monomers, and the phosphorus-containing polymerizable monomer accounts for 0.1wt% to 5wt% of the total amount of the polymerizable monomers;

[0028] Optionally, the carboxyl-containing polymerizable monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid, maleic acid, maleic acid sodium salt and maleic acid lithium salt;

[0029] Optionally, the amide-containing polymerizable monomer is selected from one or more of acrylamide, methacrylamide, N,N-methylenebisacrylamide, N-isopropylacrylamide and N-ethylacrylamide;

[0030] Optionally, the nitrile-containing polymerizable monomer is selected from one or more of acrylonitrile and methacrylonitrile;

[0031] Optionally, the phosphorus-containing polymerizable monomer is selected from one or more of phosphate-containing acrylate, allyl phosphate and phosphate-containing methacrylate. For example, the phosphorus-containing polymerizable monomer is selected from Solvay's PAM 100, PAM200, COPS-3, etc.

[0032] Optionally, the initiator includes one or more of sodium persulfate and sodium metabisulfite.

[0033] Optionally, the polymerization reaction temperature is 30°C to 80°C.

[0034] Optionally, the polymerization reaction time is 3h~7h.

[0035] After the polymerization reaction is completed, the solid product is obtained by filtering, and the solid product is also washed to obtain a polyacrylic acid copolymer.

[0036] Optionally, after incomplete drying, the method further comprises the following steps: crushing the polyacrylic acid powder binder to a particle size D 50 For example, the polyacrylic acid powder binder is crushed to a particle size D 50 20μm, 30μm, 50μm, 80μm, 100μm, 150μm, 200μm, 300μm. Particle size D 50 If the size is too small, the energy consumption of the crushing is high, and if the size is too large, the dry homogenization dissolution speed is slow. The crushing method can be grinding or grinding, and after the crushing, it also includes a screening step.

[0037] By the above method, a polyacrylic acid powder binder suitable for subsequent dry homogenization can be prepared, which has high homogenization efficiency, is conducive to the preparation of electrode plates with high peel strength and not easy to expand in volume during charging and discharging, and is conducive to the preparation of lithium-ion batteries with good cycle performance.

[0038] A second aspect of the present application provides a polyacrylic acid powder binder, which is prepared by the preparation method as described above.

[0039] Optionally, the weight average molecular weight of the polyacrylic acid powder binder is between 600,000 and 2.5 million.

[0040] Optionally, the molecular weight of the polyacrylic acid powder binder is distributed between 1.5 and 6.

[0041] Optionally, the particle size D of the polyacrylic acid powder binder is 50 20μm~300μm.

[0042] Optionally, the solid content of the polyacrylic acid powder binder is 90wt%~99wt%.

[0043] Optionally, the alcohol solvent content in the polyacrylic acid powder binder is 0.3wt%~8wt%.

[0044] The above-mentioned polyacrylic acid powder binder can be applied to the preparation of electrode plates by dry slurry process, which is beneficial to the preparation of electrode plates with high peel strength. With a small addition amount, it can exert a higher bonding force, which is beneficial to improve the battery energy density. In addition, the prepared electrode plates are not easy to expand in volume during the charge and discharge process, which is beneficial to the preparation of lithium-ion batteries with good cycle performance.

[0045] A third aspect of the present application provides a lithium-ion battery, which includes a positive electrode sheet and a negative electrode sheet, wherein the raw material for preparing at least one of the positive electrode sheet and the negative electrode sheet includes the polyacrylic acid powder binder as described above.

[0046] Optionally, the raw materials for preparing the negative electrode plate include the above-mentioned polyacrylic acid powder binder. Optionally, the raw materials for preparing the negative electrode plate also include negative electrode active materials, and the negative electrode active materials include one or more of artificial graphite, natural graphite, hard carbon and silicon carbon. The polyacrylic acid powder binder can form hydrogen bonds with the surface of the silicon negative electrode, improve the dispersion and adhesion of the negative electrode material, thereby inhibiting the volume expansion of the negative electrode active material during the charge and discharge process, and improving the performance of the SEI film to prevent the decomposition of the electrolyte during the electrochemical cycle. In the process of pursuing high energy density lithium batteries, the demand for silicon-carbon materials is increasing, and the requirements for binders for such materials are more stringent. The above-mentioned polyacrylic acid powder binder can be used as a binder for silicon-carbon negative electrodes, and has good adhesion.

[0047] Optionally, the raw materials for preparing the positive electrode sheet include the above-mentioned polyacrylic acid powder binder. Optionally, the raw materials for preparing the positive electrode sheet also include positive electrode active materials, and the positive electrode active materials include one or more of ternary positive electrode materials, lithium cobalt oxide positive electrode materials, lithium iron phosphate positive electrode materials and lithium manganese oxide positive electrode materials. DETAILED DESCRIPTION

[0048] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0050] the term

[0051] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0052] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0053] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0054] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0055] In the present application, when referring to a numerical interval (i.e., a numerical range), unless otherwise specified, the optional numerical distribution within the above numerical interval is deemed to be continuous and includes the two numerical endpoints of the numerical range (i.e., the minimum value and the maximum value), and every numerical value between the two numerical endpoints.

[0056] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0057] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.

[0058] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0059] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.

[0060] In the present application, the solid content test method of the polyacrylic acid powder binder is: take 2-3g of the polyacrylic acid powder binder to be tested, place it in a 150°C blast oven and bake it for 1h, record the mass m0 and m1 before and after baking, and the solid content = m1 / m0×100%.

[0061] In this application, D 50 The particle size test method is: using Dandong Bettersize 2600 laser particle size analyzer for testing.

[0062] In the present application, the test method for weight average molecular weight and molecular weight distribution is: using Shimadzu 20A GPC instrument, referring to the national standard GBT31816-2015 method for testing.

[0063] In the present application, the testing method of the alcohol solvent in the polyacrylic acid powder binder is: first test the solid content s1% of the polyacrylic acid powder binder, and then use a Karl Fischer moisture tester to test the water content s2% in the polyacrylic acid powder binder. The content of the alcohol solvent is 100%-s1%-s2%.

[0064] The following is further described in conjunction with specific examples and comparative examples. The raw materials involved in the following specific examples and comparative examples, if not otherwise specified, can all be sourced from commercial sources, the instruments used, if not otherwise specified, can all be sourced from commercial sources, and the processes involved, if not otherwise specified, are all conventionally selected by those skilled in the art. The compounds and sources used in the following specific examples and comparative examples are shown in Table 1.

[0065] Table 1

[0066]

[0067] Example 1

[0068] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, the steps are as follows:

[0069] Step 1, add 300 parts of deionized water to a reaction bottle, stir at 200 rpm, add polymerization monomers AA, AM, AN and PAM100 according to the mass parts shown in Table 2, and continue to introduce nitrogen for 1 hour to obtain a monomer aqueous solution; heat to 70° C., add 1 part of ammonium persulfate aqueous solution (mass fraction of 5%) to the monomer aqueous solution, react at 70° C. for 5 hours, and after the reaction is completed, wash the product twice with water of the same mass as the obtained product at room temperature to obtain a polyacrylic acid copolymer.

[0070] Step 2: add 300 parts of 1,3-butanediol to the polyacrylic acid copolymer obtained in step 1, and then add sodium carbonate aqueous solution at 40°C until the pH of the system is 7.8 for neutralization. After stirring and dispersing for 1 hour, collect the solid through a filter, remove the incompletely dried solid in a 60°C oven, crush it, sieve it, and then add 0.5 parts of 1,3-butanediol by spraying to obtain a water-soluble polyacrylic acid powder binder.

[0071] Referring to Table 3, the solid content of the polyacrylic acid powder binder obtained in this embodiment is 93wt%, the alcohol solvent content is 0.7wt%, and D 50 The particle size is 105 μm, the Mw is 1.09 million, and the molecular weight distribution is 3.35.

[0072] Example 2

[0073] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Example 1, except that: 1) each raw material is added in parts by weight as shown in Table 2; 2) the polymerization temperature of step 1 is 50° C.; 3) the pH of the neutralization treatment system of step 2 is 7.2.

[0074] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0075] Example 3

[0076] The present embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Example 1, with the main differences being: 1) the polymerization monomers are as shown in Table 2; 2) each raw material is added in parts by weight as shown in Table 2; 3) the polymerization temperature of step 1 is 30°C; 3) the neutralization treatment temperature of step 2 is 20°C; 4) the oven temperature of step 2 is 50°C.

[0077] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0078] Example 4

[0079] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Embodiment 1, except that: 1) the polymerization monomers are as shown in Table 2; 2) each raw material is added according to the mass parts shown in Table 2.

[0080] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0081] Example 5

[0082] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Embodiment 1, except that: 1) the polymerization monomers are as shown in Table 2; 2) each raw material is added according to the mass parts shown in Table 2.

[0083] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0084] Example 6

[0085] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Embodiment 1, except that: 1) the polymerization monomers are as shown in Table 2; 2) each raw material is added according to the mass parts shown in Table 2.

[0086] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0087] Example 7

[0088] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as that of Embodiment 1, except that: 300 parts of 1,3-butanediol are added in step 2, and 1,3-butanediol is not added after incomplete drying.

[0089] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0090] Example 8

[0091] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as that of Embodiment 1, except that 30 parts of 1,3-butanediol are added in step 2.

[0092] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0093] Example 9

[0094] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Embodiment 1, except that: 1) each raw material is added in parts by weight as shown in Table 2; 3) 300 parts of 1-hexanol are added in step 2.

[0095] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0096] Example 10

[0097] This embodiment provides a polyacrylic acid powder binder and a preparation method thereof, which is basically the same as Embodiment 1, with the main differences being: 1) the polymerization monomers are as shown in Table 2; 2) the raw materials are added in parts by weight as shown in Table 2; 3) 300 parts of pentaerythritol are added in step 2, and no additional pentaerythritol is added if the drying is not complete.

[0098] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0099] Comparative Example 1

[0100] This comparative example provides a polyacrylic acid binder and a preparation method thereof, which is basically the same as Example 1, except that: 1) no alcohol solvent is added; 2) no alcohol solvent is added, and step 2 is as follows:

[0101] Step 2: At 40° C., add sodium carbonate aqueous solution to the polyacrylic acid copolymer obtained in step 1 until the pH of the system is 7.8 for neutralization. After stirring and dispersing for 1 hour, filter through a filter to obtain a solution-type polyacrylic acid binder without collecting solids.

[0102] The solid content of the solution-type polyacrylic acid binder obtained in this comparative example, the Mw of the polyacrylic acid binder and the molecular weight distribution are shown in Table 3.

[0103] Comparative Example 2

[0104] This comparative example provides a polyacrylic acid powder binder and a preparation method thereof, which are basically the same as Example 1, with the main difference being that the neutralization temperature is 80°C.

[0105] The solid content, alcohol solvent content, and D 50 See Table 3 for particle size, Mw and molecular weight distribution.

[0106] Table 2

[0107]

[0108] Table 3

[0109]

[0110] The polyacrylic acid powder binders prepared in the above-mentioned embodiments and comparative examples and the solution-type polyacrylic acid binder of comparative example 1 are applied to the preparation of negative electrode sheets of lithium-ion batteries, and the steps are as follows:

[0111] At room temperature, 1 part of conductive carbon black sp and 97.2 parts of negative electrode active material (graphite) were added to a stirring tank and mixed, and then 1.8 parts of the polyacrylic acid powder binder prepared in each embodiment and comparative example and 30 parts of the solution type polyacrylic acid binder prepared in comparative example 1 were added, and added into deionized water at a ratio of 50wt% of the system solid content, and stirred and mixed thoroughly to prepare a uniform negative electrode slurry, which was coated on the negative electrode current collector Cu foil, dried, and rolled to obtain a negative electrode sheet.

[0112] The peel strength and electrochemical performance of the prepared negative electrode sheets were evaluated.

[0113] Peel strength evaluation: It is tested by a special adhesion tester. The test method of peel strength refers to the American Society for Testing and Materials standard ASTM D3330. The instrument is a Kejian tensile testing machine. The details are as follows: Cut the negative electrode into a 150mm long and 15mm wide electrode along the rolling direction. Stick a 3M double-sided tape with a width of 100mm and a width of 15mm on a smooth stainless steel plate, stick the electrode flat on the double-sided tape, roll back and forth 10 times with a 2kg rubber roller, and then fix the stainless steel plate on the tensile machine. The electrode that is not attached to the tape is reversely clamped on the tensile machine probe. The base of the tensile machine pulls the electrode at a speed of 5cm / min, and the sensor measures the peeling force during the process. The average value of each group of 5 parallel samples is the final peeling strength. Peel force = computer indication / 0.015, unit is N / m.

[0114] Electrochemical performance evaluation: The negative electrode sheet prepared by the above method and the positive electrode sheet with lithium iron phosphate as the positive electrode material are prepared and assembled into aluminum-plastic flexible packaging according to the lithium-ion battery production process familiar to technicians in this industry, and the electrochemical performance test is carried out. The details are as follows:

[0115] Determination of 1000 cycle capacity retention rate: At 25°C, 3.5V voltage range, 0.5C charging, 1.0C discharging for charge and discharge cycles, constant current method to test its capacity retention rate after 1000 cycles, capacity retention rate = 1000th cycle discharge gram capacity / 1st cycle discharge gram capacity.

[0116] Flexibility test method: The negative electrode prepared by the above method is wound in a low humidity room using a winding needle method. The diameter of the winding needle is 1 mm. The length of the crack of the test electrode is measured. The shorter the length, the better the flexibility.

[0117] Physical rebound rate of the electrode: The thickness of the rolled negative electrode is measured at h0, and then the thickness is measured at h1 after being placed for 24 hours. The physical rebound rate is (h1-h0) / h0×100%.

[0118] The above test results are shown in Table 4.

[0119] Table 4

[0120]

[0121] Combined with Comparative Example 1, it can be seen that at 40°C, the neutralization treatment is carried out without adding an alcohol solvent, and a powder binder cannot be formed. Relative to Example 7, the solution-type binder prepared in Comparative Example 1 has poorer bonding force than the powder binder prepared in Example 7, the prepared electrode has poor ability to inhibit expansion, and the prepared battery has poor cycle performance. Combined with Comparative Example 2, it can be seen that if the temperature is raised to 80°C, it will cause the powder binder to be difficult to redissolve in the aqueous slurry, resulting in difficulty in homogenization, and the electrode cannot be prepared. However, the embodiments of the present application all show better electrode processing, higher peel strength, lower electrode physical rebound and higher cycle capacity retention rate by adding alcohol solvents and controlling the neutralization treatment temperature not to exceed 60°C. It shows that the powder binder prepared under the above conditions has good bonding force and the ability to inhibit expansion, and can effectively inhibit the volume expansion of the active material in the charge and discharge cycle, thereby improving the cycle performance of the electrode electrode and lithium-ion battery.

[0122] In addition, in combination with Example 1 and Example 7, since the alcohol solvent evaporates during the incomplete drying process, the content of alcohol solvent in the final product is relatively low, resulting in the adhesive of Example 7 having poor flexibility and poor processability, resulting in a loss of bonding strength and cycle performance.

[0123] In addition, in combination with Example 1 and Example 8, when the amount of alcohol solvent added is small, a portion of the polyacrylic acid copolymer will still be hydrated during the neutralization process to form a small portion of viscous paste. After incomplete drying conditions to the same solid content, insoluble matter appears in the powder binder during the dry slurry stage, affecting the slurry stability of the negative electrode slurry, resulting in a decline in the bonding force and the ability of the electrode to inhibit expansion, and the battery's cycle performance also declines.

[0124] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0125] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a polyacrylic acid powder binder, characterized in that: The following steps are involved: Mixing polymerization monomers and initiators to generate polymerization reaction to prepare polyacrylic acid copolymers; In the presence of an alcohol solvent, the polyacrylic acid copolymer is neutralized at a temperature not exceeding 60° C. to obtain a polyacrylic acid powder binder.

2. The polyacrylic acid powder binder according to claim 1, characterized in that: The number of carbon atoms of the alcohol solvent is not less than 3; optionally, the number of carbon atoms of the alcohol solvent is between 3 and 6; optionally, the alcohol solvent is selected from one or more of 1,3-butanediol, 1,4-butanediol, 1,2-propylene glycol, 1,2-pentanediol, pentaerythritol, isopropanol, glycerol, 1-butanol, 1-pentanol, 2-butanol and 1-hexanol.

3. The polyacrylic acid powder binder according to claim 1, characterized in that: The mass of the alcohol solvent is not less than the total mass of the polymerized monomers; optionally, the mass of the alcohol solvent is 1 to 3 times the total mass of the polymerized monomers.

4. The polyacrylic acid powder binder according to claim 1, characterized in that: After neutralization, The method comprises the following steps: separating the solid and liquid of the reaction system after the neutralization treatment, and incompletely drying the obtained solid.

5. The polyacrylic acid powder binder according to claim 4, characterized in that: Includes at least one of the following features: (1) The temperature of incomplete drying shall not exceed 80°C; (2) Controlling the incomplete drying conditions so that the solid content of the polyacrylic acid powder binder is 90 wt % to 99 wt %.

6. The polyacrylic acid powder binder according to claim 4, characterized in that: After incomplete drying, the method further includes the following steps: adding the alcohol solvent to the polyacrylic acid powder binder to obtain an alcohol solvent content greater than or equal to 0.3wt%; optionally, the alcohol solvent is added to the polyacrylic acid powder binder to obtain an alcohol solvent content of 0.3wt% to 8wt%.

7. The polyacrylic acid powder binder according to any one of claims 1 to 6, characterized in that: Includes at least one of the following features: (1) controlling the conditions of the polymerization reaction and the neutralization treatment so that the weight average molecular weight of the polyacrylic acid powder binder is between 600,000 and 2.5 million; (2) Controlling the conditions of the polymerization reaction and the neutralization treatment so that the molecular weight distribution of the polyacrylic acid powder binder is between 1.5 and 6.

8. The polyacrylic acid powder binder according to any one of claims 1 to 6, characterized in that: Includes at least one of the following features: (1) The pH value of the neutralization treatment system is 6 to 9; (2) The neutralizing agent for the neutralization treatment includes an alkaline substance; optionally, the alkaline substance includes an inorganic base; optionally, the inorganic base includes one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate and potassium carbonate; (3) The polymerizable monomers include carboxyl-containing polymerizable monomers, amide-containing polymerizable monomers and nitrile-containing polymerizable monomers; optionally, the polymerizable monomers further include phosphorus-containing polymerizable monomers; (4) The initiator includes one or more of sodium persulfate and sodium metabisulfite; (5) The polymerization reaction temperature is 30°C to 80°C; (6) The polymerization reaction time is 3h~7h.

9. The polyacrylic acid powder binder according to claim 8, characterized in that: Includes at least one of the following features: (1) The carboxyl-containing polymerizable monomer accounts for 20wt% to 40wt% of the total amount of the polymerizable monomers, the amide-containing polymerizable monomer accounts for 10-35wt% of the total amount of the polymerizable monomers, the nitrile-containing polymerizable monomer accounts for 40-50wt% of the total amount of the polymerizable monomers, and the phosphorus-containing polymerizable monomer accounts for 0.1wt% to 5wt% of the total amount of the polymerizable monomers; (2) the carboxyl-containing polymerizable monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid, maleic acid, sodium maleate and lithium maleate; (3) The amide-containing polymerizable monomer is selected from one or more of acrylamide, methacrylamide, N,N-methylenebisacrylamide, N-isopropylacrylamide and N-ethylacrylamide; (4) the nitrile-containing polymerizable monomer is selected from one or more of acrylonitrile and methacrylonitrile; (5) The phosphorus-containing polymerizable monomer is selected from one or more of phosphorus-containing acrylate, allyl phosphate and phosphorus-containing methacrylate.

10. The polyacrylic acid powder binder according to any one of claims 1 to 6, characterized in that: After incomplete drying, the following steps are further included: crushing the polyacrylic acid powder binder to a particle size D 50 20μm~300μm.

11. A polyacrylic acid powder binder, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 10.

12. A lithium ion battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, and the raw material for preparing at least one of the positive electrode sheet and the negative electrode sheet comprises the polyacrylic acid powder binder according to claim 11.

Citation Information

Patent Citations

  • Preparation method and application of polyacrylic acid powder binder for lithium battery

    CN118460147A

  • Water-based adhesive for positive electrode sheet, and positive electrode sheet made by water-based adhesive

    WO2024040572A1